Escherichia coli as a sentinel in the assessment of antimicrobial resistance in the tilapia production chain: from production environment to the final product - Sthéfany Da Cunha Dias; Letícia Roberta Martins Costa; Ana Beatriz Garcez Buiatte; Marcus Vinícius Coutinho Cossi; Luís Augusto Nero; Ricardo Seiti Yamatogi; Luciano dos Santos Bersot; Juliano Gonçalves Pereira (Frontiers in Antibiotics, 2024)
IntroductionThe intensification of tilapia production has increased animal density in tanks, leading to more frequent exposure to pathogenic agents and compromising the quality of fish products. Antimicrobial resistance is a global concern that affects human treatment, and sentinel microorganisms like Escherichia coli are crucial for monitoring production chains, especially in aquaculture, where research is still limited. The aim of this study was to identify the presence of E. coli and investigate its antimicrobial resistance profiles throughout the entire tilapia production chain.MethodsA total of 240 samples were collected from various points in the production process: carcasses before scaling (Ca), scaling wastewater (Sw), filleting wastewater (Fw), fillet washing wastewater (Tw), fillet handling surfaces (Su), and pre-packaged fillets (Pf). The samples were collected during 10 visits, each corresponding to animals from different farms. E. coli isolates were identified using MacConkey agar and biochemical tests. Phenotypic resistance profiles were determined using nine classes of antimicrobials. Extended- spectrum b-lactamase (ESBL) production was identified with ceftazidime and cefotaxime and confirmed by a double-disc synergy test. Isolates were classified as sensitive or resistant based on the inhibition zone. Multidrug-resistant (MDR) was defined as resistance to at least one agent in three or more antimicrobial categories, while extensively drug-resistant (XDR) was defined as resistance to at least one agent in all but two or fewer categories.ResultsOverall, 50.8% of the samples (122/240) tested positive for E. coli, with 403 isolates identified. Of these, 33% (133/403) were resistant to at least two antimicrobials, and 20% (48/240) of the samples had MDR isolates, with the highest frequency found at the filleting point (Fw), which also had the only XDR profile. Resistance was most commonly observed against amoxicillin (35.73%), tetracycline (30.77%), and ciprofloxacin (26.30%).DiscussionThese findings emphasize the importance of E. coli as an indicator of antimicrobial resistance throughout tilapia processing and highlight the need for good production practices and qualified technical support to mitigate risks to public health, animal health, and the environment.